A theory of reversibility for Erlang - Lanese, Ivan; Nishida, Naoki; Palacios, Adrián; Vidal, Germán (Journal of logical and algebraic methods in programming, 2018)
In a reversible language, any forward computation can be undone by a finite sequence of backward steps. Reversible computing has been studied in the context of different programming languages and formalisms, where it has been used for testing and verifica- tion, among others. In this paper, we consider a subset of Erlang, a functional and concurrent programming language based on the actor model. We present a formal semantics for reversible computation in this language and prove its main properties, including its causal consistency. We also build on top of it a rollback operator that can be used to undo the actions of a process up to a given checkpoint.